Ultraphonophoresis with a hyaluronic acid-containing gel for knee osteoarthritis with periarthritis - O. N. Anoshenkova; A. N. Kalyagin; Yu. V. Maksimova; N. G. Sindykheeva; A. V. Sinkov; G. M. Sinkova (Современная ревматология, 2018)
Management of patients with knee osteoarthritis (OA) in the presence of comorbidity causes significant difficulties associated with the limitations of pharmacotherapy.Objective: to evaluate the clinical efficacy of ultraphonophoresis with a hyaluronic acid (HA)-containing gel in patients with knee OA complicated by periarthritis.Patients and methods. The open observational comparative study included 30 patients with a reliable diagnosis of knee OA, who were divided into two groups: 1) 15 patients who had undergone ultraphonophoresis with a HA-containing gel for 10 days (a study group); 2) 15 patients who had received ultraphonophoresis with an intact gel (a control group). To determine the clinical efficiency of HA-containing gel ultraphonophoresis, the investigators conducted a survey of patients and a clinical examination with knee joint palpation to detect synovitis and periarthritis, ultrasonography, and an assessment of initial pain and pain on walking on a 100-mm visual analog scale (VAS) for pain.Results and discussion. HA-containing gel ultraphonophoresis was found to lead to a significant relief from both pain in the knee joints on walking from 50 [40; 50] to 20 [10; 20] mm (p = 0.0003) and from initial pain from 50 [40; 50] to 10 [0; 10] mm VAS (p = 0.0003). Ultrasonography revealed a reduction or even complete disappearance of the local inflammatory process in the anserine bursa from 5.5 [4.5; 6.4] to 0 [0; 3.0] mm (p = 0.0003). There were no statistically significant pre- and postoperative differences in Group 2 patients.Conclusion. HA-containing gel ultraphonophoresis in knee OA with periarthritis was shown to contribute to a significant reduction in knee joint pain and to the resolution of periarthritis.Management of patients with knee osteoarthritis (OA) in the presence of comorbidity causes significant difficulties associated with the limitations of pharmacotherapy.Objective: to evaluate the clinical efficacy of ultraphonophoresis with a hyaluronic acid (HA)-containing gel in patients with knee OA complicated by periarthritis.Patients and methods. The open observational comparative study included 30 patients with a reliable diagnosis of knee OA, who were divided into two groups: 1) 15 patients who had undergone ultraphonophoresis with a HA-containing gel for 10 days (a study group); 2) 15 patients who had received ultraphonophoresis with an intact gel (a control group). To determine the clinical efficiency of HA-containing gel ultraphonophoresis, the investigators conducted a survey of patients and a clinical examination with knee joint palpation to detect synovitis and periarthritis, ultrasonography, and an assessment of initial pain and pain on walking on a 100-mm visual analog scale (VAS) for pain.Results and discussion. HA-containing gel ultraphonophoresis was found to lead to a significant relief from both pain in the knee joints on walking from 50 [40; 50] to 20 [10; 20] mm (p = 0.0003) and from initial pain from 50 [40; 50] to 10 [0; 10] mm VAS (p = 0.0003). Ultrasonography revealed a reduction or even complete disappearance of the local inflammatory process in the anserine bursa from 5.5 [4.5; 6.4] to 0 [0; 3.0] mm (p = 0.0003). There were no statistically significant pre- and postoperative differences in Group 2 patients.Conclusion. HA-containing gel ultraphonophoresis in knee OA with periarthritis was shown to contribute to a significant reduction in knee joint pain and to the resolution of periarthritis.